Public relations for law firms in Singapore - Ang, Lay Peng (2008)
The overall marketing effort generally requires both Public Relations (PR) and advertising. This study seeks to find out the extent to which PR can improve the public's perception and understanding of law firms in Singapore. It also explores advertising as a marketing technique in today's competitive legal environment.